Possible effects of Botox on the skin of laboratory rats - Rania kareem Abd,; Satar Abood Faris, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Botulinum toxin is a polypeptide chain consisting of a heavy chain (100 kDa) and a light chain (50 kDa). Botox consists of 7 types of neurotoxins, however only toxins A and B are used clinically .The current study was conducted on (18) samples of female laboratory rats divided into five groups, with 6 rats per group, where they were injected with different concentrations of Botox. These groups include: Group A, which is the control group, Group B, which was injected with a concentration of 0.025 of Botox, Group C, which was injected with a concentration of 0.2,.The results of the statistical analysis showed a significant decrease (p≤0.05) in the average thickness of the skin layers. Botox injections affect the thickness of the skin layers without being affected by the injection dose .